Xantine oxidase inhibition activity of infusion and ethanol extract of white tea - Ardi Rustamsyah; Sarah Nur Islami; Fitriana Fitriana; Mimin Kusmiyati (Jurnal Penelitian Teh dan Kina, 2016)
Research of xantine oxidase enzyme inhibition activity of infusion and ethanol extract of white tea were done. The aim of this research was to evaluateÂ  xantine oxidase inhibitory activity of infusion and ethanol extract of white tea. Phytochemical screening on dry tea, infusion and ethanol extract of white tea showed that all samples contained alkaloid, flavonoid, quinone, tannin and tritherpenoid/ steroide. The IC50 value of samples were 76,64 Î¼g/ml and 31,11Î¼g/ml respectivelly. This study used allopurinol as standard with IC50 was 0,60 Î¼g/ml.